2023
DOI: 10.5194/acp-23-587-2023
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the radiative effect of Arctic cirrus measured in situ during the winter 2015–2016

Abstract: Abstract. The radiative energy budget in the Arctic undergoes a rapid transformation compared with global mean changes. Understanding the role of cirrus clouds in this system is vital, as they interact with short- and long-wave radiation, and the presence of cirrus can be decisive as to a net gain or loss of radiative energy in the polar atmosphere. In an effort to derive the radiative properties of cirrus in a real scenario in this sensitive region, we use in situ measurements of the ice water content (IWC) p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The lower N observed in HL cirrus compared to ML cirrus is consistent with the observations from Wolf et al (2018). Marsing et al (2023) showed averaged IWCs (0.003 and 0.005 g m −3 ) of two case studies during the POLSTRACC (Polar Stratosphere in a Changing Climate) campaign in line with our measurements at high latitudes.…”
Section: Overview and Differences In Microphysical Properties Of Cirr...supporting
confidence: 91%
See 1 more Smart Citation
“…The lower N observed in HL cirrus compared to ML cirrus is consistent with the observations from Wolf et al (2018). Marsing et al (2023) showed averaged IWCs (0.003 and 0.005 g m −3 ) of two case studies during the POLSTRACC (Polar Stratosphere in a Changing Climate) campaign in line with our measurements at high latitudes.…”
Section: Overview and Differences In Microphysical Properties Of Cirr...supporting
confidence: 91%
“…In this study we provide new insights into the microphysical properties of the rarely observed Arctic cirrus and support our analysis by backward trajectories of the cirrus air parcels to investigate cirrus formation and evolution. Even though other campaigns have been previously performed in this region (Schiller et al, 2008;Heymsfield et al, 2013;Krämer et al, 2016;Wolf et al, 2018;Marsing et al, 2023), in situ data on the full range of cirrus particle sizes remain limited at high latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, clouds absorb a portion of shortwave radiation, scatter another portion and reflect the rest back into space, thereby altering the amount of solar radiation reaching Earth's surface. Cirrus clouds, due to their high altitude and composition of ice crystals, exhibit strong scattering of shortwave radiation and also significantly affect the emission and absorption of longwave radiation (Marsing et al, 2023;Shi and Liu, 2016). Cumulus clouds, with their rough structure, contribute to strong scattering and some degree of absorption of shortwave radiation.…”
Section: Discussion On Clouds and Solar Radiationmentioning
confidence: 99%
“…Due to their influence on the radiative energy budget in the Arctic (Marsing et al, 2023), cirrus need to be properly represented in numerical weather prediction (NWP) models. One important component of each NWP model considers the atmospheric radiative transfer, calculating the radiative energy budget and atmospheric heating and cooling rates as a driver for dynamic processes.…”
Section: Introductionmentioning
confidence: 99%